Pelayanan Informasi Publik Pemerintah Kota Bukittinggi Melalui Media Relations - Qalby De Rekha, Futihat; Syamsir, Syamsir (Policy, Law and Political Research Center, 2024)
This research aims to determine the form of public information services of the Bukittinggi City Government and the cooperation between the Bukittinggi City Government and the press media in optimizing the dissemination of public information. The location of this research is the Bukittinggi City Regional Secretariat Office in the Bukittinggi City Diskominfo section. Data collection used in this research was done through observation, interviews, and documentation. The results show that the form of public information service used by the Bukittinggi City Government is to establish cooperative relationships with the press media to spread the news more widely, and it is hoped that information can be distributed evenly to the public. The effectiveness and utilization of media relations are significant for disseminating information to the public so that the public's right to obtain information from the government can be fulfilled. This research concludes with the use and effectiveness of press media in helping the government disseminate information related to Bukittinggi City Government programs.